Treatment goals and preferences of pediatric atopic dermatitis patients, young adults, and caregivers - Lisa P. van der Rijst; Marjolein S. de Bruin-Weller; Nicolaas P. A. Zuithoff; Saskia Spillekom-van Koulil; Marieke M. B. Seyger; Marlies de Graaf (Journal of Dermatological Treatment)
Purpose: Understanding the treatment goals and preferences of young atopic dermatitis (AD) patients and their caregivers is crucial for enhancing patient-centered care. This study aims to identify these goals and preferences and explore heterogeneity among subgroups.Materials and methods: A web-based survey was conducted among children (6–11 years), adolescents (12–17 years), and young adults (18–30 years) with AD and caregivers of AD patients. Survey questions included multiple-choice, four-point Likert scale, and open-ended questions. Goals and preferences were stratified by age, gender, disease severity, current treatment, visible lesions, and atopic comorbidity.Results: A total of 286 respondents were included. Prioritized treatment goals were ‘no itch’, ‘preventing new lesions’, and ‘no lesions’. Prioritized treatment characteristics were ‘high effectiveness’ and ‘long-term safety’. Young patients (6–30 years) considered convenience of treatment more important than caregivers, while caregivers considered short- and long-term safety more important than young patients. Pediatric patients (6–17 years) considered psychosocial goals more important than young adults. Goals and preferences also differed by disease severity, gender, current treatment, and atopic comorbidity.Conclusions: Young AD patients and caregivers strive to reduce itch and lesions with effective and safe treatment. Goals and preferences differ within individuals at different stages of life, highlighting the importance of addressing individual needs to improve patient-centered care.